Scale invariance of structural transformations in plastically deformed nanostructured solids; Physical Mesomechanics; Vol. 20, iss. 1 - Panin V. E. Viktor Evgenyevich; Panin A. V. Alexey Viktorovich; Pochivalov Yu. I. Yury Ivanovich; Elsukova T. F. Tamara Fillipovna; Shugurov A. R. Artur Rubinovich (2017, 2017)
Title screen